3 2 ( e 2 x + y + e 2 y + z + e 2 z + x ) − 3 e x + e y + e z
For some real numbers x , y , z that satisfies the condition x + y + z = 6 and the maximum value of above expression is M . Find ⌊ 1 0 0 0 M ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Lakshya Sinha I wonder why applying C a u c h y − S h w a r t z or A M − G M to the first part yields the same answer.
I did not use A M − G M else you would have asked for a proof. I know why both maximum and minimum values are equal, this time I am asking you for a proof. It should be easy for you.
Log in to reply
Dude I must tell you that I created a weaker inequality at first then I solved as you did and then I used the theorem as mentioned in my solution
Let X = 3 2 ( e 2 x + y + e 2 y + z + e 2 z + x ) − 3 e x + e y + e z
It is shown later that when x = y = z = 2 , X maximizes when Y = e 2 x + y + e 2 y + z + e 2 z + x is maximum and Z = e x + e y + e z is minimum.
Using RMS-AM inequality on Y
3 e 2 x + y + e 2 y + z + e 2 z + x ≤ 3 e x + y + e y + z + e z + x ≤ e 2 At equality x = y = z = 2
Applying AM-GM inequality on Z
3 e x + e y + e z ≥ 3 e x + y + z = 3 e 6 = e 2
Again equality occurs when x = y = z = 2 .
Therefore, X m a x = 2 e 2 − e 2 = e 2 ≈ 7 . 3 8 9 ⟹ ⌊ 1 0 0 0 M ⌋ = ⌊ 1 0 0 0 × 7 . 3 8 9 ⌋ = 7 3 8 9
Problem Loading...
Note Loading...
Set Loading...
One needs to maximise the first part and minimise the second part in order to get maximum value of the whole expression.
For the second part:
( 3 e x + e y + e z ) m i n
Applying A M − G M and also the condition for equality x = y = z = 2 :
= 3 e 2 ⋅ e 2 ⋅ e 2
= e 2
For the first part:
( 3 2 ( e 2 x ⋅ e 2 y + e 2 y ⋅ e 2 z + e 2 z ⋅ e 2 x ) ) m a x
Applying Cauchy-Shwartz inequality and also applying the condition for equality x = y = z = 2 :
= 3 2 ( ( ( e 2 x ) 2 + ( e 2 y ) 2 + ( e 2 z ) 2 ) ⋅ ( ( e 2 x ) 2 + ( e 2 y ) 2 + ( e 2 z ) 2 ) )
= 3 2 ( 3 e 2 ) ⋅ ( 3 e 2 )
= 3 2 × ( 3 e 2 )
= 2 e 2
Hence, the maximum value of the given expression boils down to:
M = ( 2 e 2 ) − ( e 2 )
M = e 2 = 7 . 3 8 9 1
⇒ ⌊ 1 0 0 0 M ⌋ = 7 3 8 9